Predictive Value of Preoperative Hypersensitive C-Reactive Protein in the Incidence of Postoperative Cognitive Impairment in Valvular Disease Patients: A Retrospective Study - Zhao A; Peng Y; Lin L; Chen L; Lin Y (Journal of Inflammation Research)
Ani Zhao,1,* Yanchun Peng,2,* Lingyu Lin,2 Liangwan Chen,3,4 Yanjuan Lin2,3 1School of Nursing, Fujian Medical University, Fuzhou, Fujian, People’s Republic of China; 2Department of Nursing, Fujian Medical University Union Hospital, Fuzhou, Fujian Province, 350001, People’s Republic of China; 3Department of Cardiovascular Surgery, Fujian Medical University Union Hospital, Fuzhou, Fujian Province, 350001, People’s Republic of China; 4Key Laboratory of Cardio-Thoracic Surgery (Fujian Medical University) Fujian Province University, Fuzhou, Fujian Province, 350001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Liangwan Chen, Department of Cardiovascular Surgery, Fujian Medical University Union Hospital, 29 Xinquan Road, Fuzhou, Fujian Province, 350001, People’s Republic of China, Email fjxhlwc@163.com Yanjuan Lin, Department of Nursing, Fujian Medical University Union Hospital, 29 Xinquan Road, Fuzhou, Fujian Province, 350001, People’s Republic of China, Email fjxhyjl@163.comObjective: Postoperative cognitive dysfunction (POCD) is associated with adverse outcomes of cardiac surgery. This study investigated the potential of pre-operative hypersensitive C-reactive protein (Hs-CRP) as a prognostic indicator of POCD in valvular disease (VHD).Methods: This study retrospectively analyzed 372 VHD patients admitted to the Department of Cardiac Surgery, Fujian Medical University Union Hospital from January 2024 to July 2024. POCD was evaluated by neuropsychological examination before and one month after surgery. Demographics, disease history, blood biochemical parameters, and perioperative data were collected. Patients were divided into a POCD group (N = 103) and a non-POCD group (N = 269) according to the occurrence of POCD. A logistic regression model was used to analyze the relationship between Hs-CPR and POCD in VHD patients.Results: The 1-month incidence of POCD in VHD patients was 27.6%. There was statistical significance in age and years of education between the two groups (P = 0.047, P = 0.001). The red blood cell count in the POCD group was lower than that in the non-POCD group (P = 0.025), and the Hs-CRP and mechanical ventilation duration in the POCD group was higher than that in the non-POCD group, with statistical significance (P < 0.001). No significant differences were observed in the results of demographic characteristics and other laboratory measures. The incidence of hospitalization days, ICU stay time, acute renal insufficiency, and new cerebral infarction in the POCD group were higher than those in the non-POCD group (P < 0.001, P < 0.001, P = 0.001, P = 0.029). Univariate and multivariate analysis showed that Hs-CRP was an independent risk factor for POCD in patients undergoing surgery for VHD disease.Conclusion: Our study shows that preoperative Hs-CRP is significantly elevated in POCD patients undergoing VHD surgery, and preoperative Hs-CRP is an independent predictor of POCD.Keywords: valvular heart disease, VHD, Hs-CRP, postoperative cognitive complications, cognitive dysfunction, postoperative cognitive dysfunction